Determination of Voriconazole Plasma Concentration by HPLC Technique and Evaluating Its Association with Clinical Outcome and Adverse Effects in Patients with Invasive Aspergillosis. (13th April 2021) - Yousefian, Sahar; Dastan, Farzaneh; Marjani, Majid; Tabarsi, Payam; Barati, Saghar; Shahsavari, Nahid; Kobarfard, Farzad
Abstract : Purpose . Invasive aspergillosis is a prevalent fungal disease, especially in Asian countries with a high mortality rate. Voriconazole (VRZ) is the first choice for invasive aspergillosis treatment. Plasma concentration of this drug is unpredictable and varies among individuals. This variability is influenced by many factors leading to clinical implication. Therapeutic drug monitoring (TDM) may have a crucial role in the patients' treatment process. The HPLC method provides sufficient specificity and sensitivity for plasma VRZ concentration determination for TDM purposes of this drug. Methods . Patients who initiated oral or intravenous VRZ for invasive aspergillosis were enrolled in this study. Demographic characteristics and clinical data, outcome, and adverse effects were documented. For each patient, the plasma sample was collected under steady-state condition and analyzed using a validated HPLC method. Results . A total of 22 measurements were performed. Fifty percent of patients were out of the therapeutic range. From them, 27.27% and 22.73% were in subtherapeutic and supratherapeutic ranges (<1  μ g/mL and >5.5  μ g/mL), respectively. There was a significant correlation between VRZ plasma concentration and treatment outcomes (P = 0.022 ). Treatment failure was five times higher than treatment success in those in the subtherapeutic range. Adverse effects were observed more frequently in patients with supratherapeutic concentrations compared to those with non-supratherapeutic levels. Furthermore, the mortality rate in patients experiencing treatment failure was 2.17 times higher than those with treatment success. Conclusions . TDM of VRZ plays an important role in better evaluation of efficacy and toxicity during treatment. Therefore, determination of the drug level may be of clinical significance.